Antibody Detection and Molecular Characterization of Toxoplasma gondii from Bobcats (Lynx rufus), Domestic Cats (Felis catus), and Wildlife from Minnesota, USA. (2nd March 2016) - Verma, Shiv K.; Minicucci, Larissa; Murphy, Darby; Carstensen, Michelle; Humpal, Carolin; Wolf, Paul; Calero‐Bernal, Rafael; Cerqueira‐Cézar, Camila K.; Kwok, Oliver C.H.; Su, Chunlei; Hill, Dolores; Dubey, Jitender P.
Abstract: Little is known of the epidemiology of toxoplasmosis in Minnesota. Here, we evaluated Toxoplasma gondii infection in 50 wild bobcats ( Lynx rufus ) and 75 other animals on/near 10 cattle farms. Antibodies to T. gondii were assayed in serum samples or tissue fluids by the modified agglutination test (MAT, cut‐off 1:25). Twenty nine of 50 bobcats and 15 of 41 wildlife trapped on the vicinity of 10 farms and nine of 16 adult domestic cats ( Felis catus ) and six of 14 domestic dogs resident on farms were seropositive. Toxoplasma gondii oocysts were not found in feces of any felid. Tissues of all seropositive wild animals trapped on the farm were bioassayed in mice and viable T. gondii was isolated from two badgers ( Taxidea taxus ), two raccoons ( Procyon lotor ), one coyote ( Canis latrans ), and one opossum ( Didelphis virginiana ). All six T. gondii isolates were further propagated in cell culture. Multi‐locus PCR‐RFLP genotyping using 10 markers (SAG1, SAG2 (5′‐3′SAG2, and alt.SAG2), SAG3, BTUB, GRA6, c22‐8, c29‐2, L358, PK1, and Apico), and DNA from cell culture derived tachyzoites revealed three genotypes; #5 ToxoDataBase (1 coyote, 1 raccoon), #1 (1 badger, 1 raccoon, 1 opossum), and #2 (1 badger). This is the first report of T. gondii prevalence in domestic cats and in bobcats from Minnesota, and the first isolation of viable T. gondii from badger.